(3OjhGf aj GdcjejGAs - (3eMeO Hf Ydj Hf eMeO Hf YQHj , CHh HcQ GdMGJej GdWGFj GdCfOdSj, GdeYQha HeMjj GdOjf GHf YQHj,J (B638 (3g` s
(3ChdgG (B:s
(3bUjOI deMji GdOjf eMeO Hf Ydi GdYQHi eWGdYgG jG WGdH GdCSQGQ ai GdCSeGA Ef GdPi jHZjg YfO GdeGA s
(3BNQgG (B:s
(3HjGf UhQI ejRGf JhVjM eG JbOe (B[ (3ai GdbUjOI (B] s
(3jJVef bUGFO ai GdcjejGA deMji GdOjf Hf GdYQHi hCHi GdajV Pi Gdfhf GdCNejei heDjO GdWZQGFis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B45 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(1590ADD) s
Keywords: (3GdcjejGA h GdWHjYjGJs